Crop-livestock competition in the West African derived savanna: Application of a multi-objective programming model - Okoruwa, V.; Jabbar, M.A.; Akinwumi, J.A. (Elsevier, 1996)
In West Africa, crop-livestock mixed farming is emerging from the currently predominant nomadic pastoralism. It is hypothesized that competitiveness between crop and livestock enterprises may be an important determinant of the pace of this evolution. A field study in the derived savanna of southwest Nigeria shows that at the current stage of evolution, as a crop farmer adds livestock to his business, there is a small gain in the beginning, then an increasing rate of substitution between crop and livestock follow. As a livestock rearer engages in crop production, there is a decreasing rate of substitution between livestock and croThis situation derives from the fact that crop production is more intensive than livestock production, which depends principally on grazing natural pastures. Results indicate that if increased population pressure and cropping intensity severely limit access to grazing land, farm and herd sizes will become smaller, then the degree of integration between crop and livestock will increase significantly.